Escalation of Commitment: Supporting Role from Accountants - Agil Novriansa; Ahmad Subeki; Aryanto Aryanto (Faculty of Economics, Universitas Sriwijaya, 2020)
Previous research has mostly examined the phenomenon of escalation of commitment in the context of decision making by managers in an investment project. However, in the capital budgeting process, before making investment decisions managers tend to consider information produced by accountants. This study examines the phenomenon of escalation of commitment using the perspective of supporting role of accountants as the party that provides information for investment decision making by managers, especially in the presence of sunk costs. This study uses a laboratory experimental method. The sample in this study are 156 undergraduate students majoring in Accounting who had passed Financial Accounting and Management Accounting courses. Based on the results of the independent sample t-test, it shows that accountants who experienced sunk cost conditions tend to provide reports that directed managers towards escalation of commitment behavior compared to accountants who do not experience sunk cost conditions. The presence of sunk cost makes accountants have better mind frame to get the possibility of profit compared with a definite loss so that the decisions they make tend to provide reports that lead to the escalation of commitment behavior